RADI-18. Survival and disease control after upfront stereotactic radiosurgery for brain metastases from breast cancer. (9th August 2021) - Wang, Yan; An, Ran; Wang, Fuchenchu; Gao, Chao; Raghavendra, Akshara Singareeka; Kim, Yon Son Betty; Briere, Tina Marie; Amaya, Diana N; Li, Jing
Abstract: Background: As systemic therapy for metastatic breast cancer (BC) improves, the survival benefit from hormonal and targeted therapy urges treatment of brain metastases (BMs) with minimal toxicity and less systemic therapy interruption. Here we assessed clinical outcomes in BC patients who received upfront stereotactic radiosurgery (SRS). Methods: We identified 236 patients who received upfront SRS with/without surgery for BMs from metastatic BC from 06/2007 to 05/2018. Twenty-four patients who received SRS for surgical cavity were excluded for analysis. Overall survival (OS) and salvage radiation-free survival (SRFS) were estimated using Kaplan-Meier analysis. Cox proportional hazard regression was used to identify prognostic factors. Results: At a median follow-up time of 15.4 months (range, 0.8–119.6), the estimated median OS was 18.5 mo (95% CI, 14.9–21). Factors associated with OS on multivariate analysis (MVA) were molecular subtypes (12.2 months for triple-negative [n=68], 13.3 months for HR+/HER2- [n=66], 36.4 months for HR+/HER2+ [n=46], and 28.1 months for HER2+ [n=32], p =0.002), KPS >80 ( p <0.0001), receipt of chemotherapy ( p =0.016) or anti-HER2 therapy ( p =0.029) after diagnosis of BM, and type of salvage radiation ( p <0.0001). OS was comparable in patients who received upfront SRS to less or more than 4 lesions (19.3 months for <4 [n=162] vs. 17.8 months for >/= 4 [n=50], p =0.36). The 12-month salvage RT rate was 25% for WBRT and 26.4% for SRS. The median SRFS was 7.4 months (95% CI, 6.5‒8.3). Factors associated with SRFS on MVA were subtypes ( p =0.002), KPS ( p =0.011), and receipt of hormone therapy after diagnosis of BM (p=0.031). Conclusions: The median OS for BC patients who developed BM is over 15 months. Molecular subtypes (HER2+ and HR+/HER2+), good KPS, and anti-HER2 or hormone therapy predicted better OS and SRFS. Prospective studies are needed to verify these results and refine the best treatment strategies for these patients.